Antibacterial Test of Skinâs and Gastric Mucosaâs Extract from Frog Duttaphrynus melanostictus Against Methicillin-resistant Staphylococcus aureus (MRSA) Isolated from RSUD Dr. Moewardi - Sejati, Nanda Eka Sri; ., Hudiyono; Indarto, Dono (Nexus Biomedika, 2016)
Introduction : Methicillin-resistant Staphylococcus aureus (MRSA) is Â now becoming global public health Â problem. Meanwhile, new antibiotics development rate is limited. Duttaphrynus melanostictusâs skin secretion was known to have antibacterial effect against some gram negative and gram positive bacterias, but cannot inhibit MRSA. This study aimed to investigate whether there is any antibacterial effects from skinâs and gastric mucosaâs extract of Duttaphrynus melanostictus against MRSA isolated from RSUD Dr. Moewardi. Methods : Antibacterial effect was tested with disc diffusion method. The extracted specimens were dorsal skin, ventral skin, and gastric mucosa. Each groups were divided into three category : 25.00 % concentration of extract, 2.50 % concentration of extract, and 1.25 % concentration of extract. Extracts were tested against MRSA from RSUD Dr. Moewardi and Staphylococcus aureus ATCC 25923 Â as control. Clear zone diameter of each groups was compared with 10.00% , 1.00%, and 0.50% acetic acid and analyzed with nonparametric Mann Whitney test (Î± = 0.05). Results : Average of clear zone diameter from skinâs extract and gastric mucosaâs extract against MRSA from concentration 25.00%, 2.50%, 1.25%Â was : ventral (35.83 Â± 0.24 mm; 12.00 Â± 0.16 mm; 7.08 Â± 0.10 mm), dorsal (19.00 Â± 0.41 mm; 7.40 Â± 0.11 mm; 7.20 Â± 0.04 mm),andÂ gastric mucosa (19.01 Â± 0.41 mm; 6.08 Â± 0.10 mm; 6.90 Â± 0.07mm). Mann Whitney test of antibacterial effect between extract and acetic acid showed ventral skinâs extract from all groups was significantly different with p = 0.020 (25.00 % ventral skinâs extractÂ compared with 10.00 % acetic acid), p = 0.020 (2.50 % ventral skinâs extract compared with 1.00% acetic acid) and p = 0.019 (1.25% ventral skinâs extract compared with 0.50% acetic acid). Meanwhile, dorsalâs skin extract was significantly different in concentration 2.50% (p = 0.021) and 1.25% (p = 0.019). Gastric mucosaâs extract was significantly different in concentration 1.25% (p= 0.019). No difference of antibacterial effect from extract against both MRSA and MSSA (p = 0.974). Conclusion: Ventral skin extract from Duttaphrynus melanostictus had the most excellent antibacterial effects and was able to inhibit the growth of MRSA. Keyword : AMP, Duttaphrynnus melanostictus, MRSA, Ventral SkinÂ